To solve for m in the equation -7m = 42, we need to isolate the variable m by dividing both sides of the equation by -7.
So, when we divide -7m = 42 by -7, we get:
m = -42/7
Simplifying further, we have:
m = -6
Therefore, the solution to the equation -7m = 42 is m = -6.
Solve for m -7m = 42
15 answers
k/-2 = -10
solve for k
solve for k
To solve for k in the equation k/-2 = -10, we need to isolate the variable k by multiplying both sides of the equation by -2.
So, when we multiply k/-2 = -10 by -2, we get:
-2 * (k/-2) = -2 * (-10)
Simplifying further, we have:
k = 20
Therefore, the solution to the equation k/-2 = -10 is k = 20.
So, when we multiply k/-2 = -10 by -2, we get:
-2 * (k/-2) = -2 * (-10)
Simplifying further, we have:
k = 20
Therefore, the solution to the equation k/-2 = -10 is k = 20.
5y - 10 = -25
solve for y
solve for y
To solve for y in the equation 5y - 10 = -25, we need to isolate the variable y by performing the necessary operations to one side of the equation.
First, we add 10 to both sides of the equation:
5y - 10 + 10 = -25 + 10
Simplifying gives:
5y = -15
Next, we divide both sides of the equation by 5:
(5y)/5 = (-15)/5
Simplifying further:
y = -3
Therefore, the solution to the equation 5y - 10 = -25 is y = -3.
First, we add 10 to both sides of the equation:
5y - 10 + 10 = -25 + 10
Simplifying gives:
5y = -15
Next, we divide both sides of the equation by 5:
(5y)/5 = (-15)/5
Simplifying further:
y = -3
Therefore, the solution to the equation 5y - 10 = -25 is y = -3.
solve for x
-3x + 4 = -8
-3x + 4 = -8
To solve for x in the equation -3x + 4 = -8, we need to isolate the variable x by performing the necessary operations to one side of the equation.
First, we subtract 4 from both sides of the equation:
-3x + 4 - 4 = -8 - 4
Simplifying gives:
-3x = -12
Next, we divide both sides of the equation by -3 to solve for x:
(-3x) / -3 = (-12) / -3
Simplifying further:
x = 4
Therefore, the solution to the equation -3x + 4 = -8 is x = 4.
First, we subtract 4 from both sides of the equation:
-3x + 4 - 4 = -8 - 4
Simplifying gives:
-3x = -12
Next, we divide both sides of the equation by -3 to solve for x:
(-3x) / -3 = (-12) / -3
Simplifying further:
x = 4
Therefore, the solution to the equation -3x + 4 = -8 is x = 4.
Solve for w
-0.1 + 23.2 = -0.8
-0.1 + 23.2 = -0.8
This equation does not contain the variable w, so it cannot be solved for w. The given equation is already solved for the given expression.
-0.1w + 23.2 = -0.8
To solve for w in the equation -0.1w + 23.2 = -0.8, we need to isolate the variable w by performing the necessary operations to one side of the equation.
First, we subtract 23.2 from both sides of the equation:
-0.1w + 23.2 - 23.2 = -0.8 - 23.2
Simplifying gives:
-0.1w = -24
Next, we divide both sides of the equation by -0.1 to solve for w:
(-0.1w) / -0.1 = (-24) / -0.1
Simplifying further:
w = 240
Therefore, the solution to the equation -0.1w + 23.2 = -0.8 is w = 240.
First, we subtract 23.2 from both sides of the equation:
-0.1w + 23.2 - 23.2 = -0.8 - 23.2
Simplifying gives:
-0.1w = -24
Next, we divide both sides of the equation by -0.1 to solve for w:
(-0.1w) / -0.1 = (-24) / -0.1
Simplifying further:
w = 240
Therefore, the solution to the equation -0.1w + 23.2 = -0.8 is w = 240.
What is the first operation used in solving this equation?
m/10 - 12 = -24
m/10 - 12 = -24
The first operation used in solving the equation m/10 - 12 = -24 is adding 12 to both sides of the equation.
Cody has 22 rare coins. Each year Cody plans to add 15 coins to his collection. How many years will it take Cody to collect 577 coins?(1 point)
To determine how many years it will take Cody to collect 577 coins, we need to set up an equation based on the given information.
Let x be the number of years it will take Cody to collect 577 coins.
In the first year, Cody has 22 coins.
In the second year, Cody will have 22 + 15 coins.
In the third year, Cody will have 22 + 2(15) coins.
And so on.
Generalizing this pattern, we can write the equation:
22 + 15x = 577
To solve for x, we need to isolate the variable x by performing the necessary operations to one side of the equation.
First, subtract 22 from both sides:
22 + 15x - 22 = 577 - 22
Simplifying gives:
15x = 555
Next, divide both sides of the equation by 15 to solve for x:
(15x)/15 = 555/15
Simplifying further:
x = 37
Therefore, it will take Cody 37 years to collect 577 coins.
Let x be the number of years it will take Cody to collect 577 coins.
In the first year, Cody has 22 coins.
In the second year, Cody will have 22 + 15 coins.
In the third year, Cody will have 22 + 2(15) coins.
And so on.
Generalizing this pattern, we can write the equation:
22 + 15x = 577
To solve for x, we need to isolate the variable x by performing the necessary operations to one side of the equation.
First, subtract 22 from both sides:
22 + 15x - 22 = 577 - 22
Simplifying gives:
15x = 555
Next, divide both sides of the equation by 15 to solve for x:
(15x)/15 = 555/15
Simplifying further:
x = 37
Therefore, it will take Cody 37 years to collect 577 coins.